Implementation of the Living Hadith ‘Cleanliness Is Part of Faith’ in the School Culture at MI Al-Huda Karangnongko - Sa'adah, Rofiatus; Haqiah, Nur Azizatul; Marhumah (Yayasan Tahfidzul Qur'an Al-Fawwaz, 2026)
This study explores the implementation of the living hadith “Cleanliness is part of faith” within the school culture at MI Al-Huda Karangnongko. Using a qualitative descriptive approach, data were collected through observations, interviews, and documentation involving students and teachers as key informants. The data were analyzed using the Miles and Huberman interactive model and validated through triangulation. The findings indicate that the hadith is not only understood as a religious teaching but is also practiced consistently through daily routines such as cleaning classrooms, maintaining personal hygiene, and participating in school-wide cleanliness activities. This implementation contributes to shaping students' character, responsibility, and awareness of cleanliness both at school and at home. The study is expected to provide insight into how living hadith practices can support religious education and character development in Islamic educational institutions.